An Empirical Assessment of Factors Affecting Professional Commitment Among Auditors and Managers in Indonesia - Bambang Riyanto L.S. (The Indonesian Journal of Accounting Research, 2013)
The financial scandals that happened in the last fifteen years reflected the tendency of executives to promote their self-interest at the expense of shareholders’ interest, or more generally public’s interests. Scholars argue that this self-serving and unethical behavior indicate the domination of commercial greed over objectively professional judgment among executives and professionals; commercial greed has, slowly but surely, replaced professional judgment.This paper is designed to test empirically the impact of work setting (i.e., managers and auditors), questioning mind, suspension of judgment, age, and work experience on professional commitment among accountants and managers in Indonesia. It is hypothesized that professional commitment is affected by work setting, suspension of judgment, questioning mind, age, and tenure. Questionaires, accompanied with cover letter, are distributed to 137 repondents (61 auditors and 76 managers). Nine questionnaires are not included in the analysis because they are not completed properly by repondents (some of the questions are not answered). The final sample comprises of 128 respondents (55 auditors and 73 managers). The findings confirm the predictions that professional commitment is affected by suspension of judgement, questioning mind, and age. Empirical evidence about the impact of these four independent variables on professional commitment is important given the public concerns about the deterioriating professionalism among public accountants and executives, as a result of the mega financial scandals that had happened around the globe in the last fifteen years.